Trends in collective bargaining coverage: stability, erosion or decline? - Visser, Jelle; Hayter, Susan; Gammarano, Rosina (Geneva, 2017)
"Collective bargaining over wages and other working conditions between unions and employers is a key labour market institution in democratic societies. The coverage and impact of this institution varies over time and across countries. This issue brief examines differences in collective bargaining coverage for 75 countries. Inclusive bargaining, conducted by unions and employers’ organizations received significant public policy support during the interwar Depression and after 1945. By contrast, collective bargaining has come under pressure in many countries since the financial crisis of 2008. This followed a longer-term decline in union membership rates. Countries in which collective bargaining coverage remained stable or increased are those that supported inclusive collective bargaining through a range of policy measures."